ANALISIS PENGARUH MANAJEMEN KELAS TERHADAP DISIPLIN BELAJAR KELAS - Haya Difa Nabilah,; Rizky Setiowati,; Salsabila Zuhra Khairunnisa,; Arita Marini, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study is a research development aimed at knowing the description of the implementation of class management and student learning discipline and whether there is influence of class management on student learning discipline at SDN Lubang Buaya 04 Pagi. This study used qualitative methods and data collection techniques used were observation, interviews and literature studies. In this research interview, the homeroom teacher and 43 students of class IV A SDN Lubang Buaya 04 Pagi were involved. Based on the research, it can be seen that the results of the research show: (1) class management is in the fairly effective category, (2) student learning discipline is in the moderate category, and (3) there is a significant effect of class management on student learning discipline, meaning that student learning discipline can be improved through classroom management carried out by the teacher. Keywords: Student Learning Outcomes, Class Management, student discipline